O ENSINO DE FILOSOFIA EMANCIPATÓRIO EM JACQUES RANCIÈRE: Uma proposta didático-filosófica para ensinar e aprender Filosofia no Ensino Médio - Tavares, Alexon Silva (2020)
This work is the result of a theoretical-practical research that aimed to establish an approximation between Rancière's thinking and the Teaching of Philosophy. The study aimed to analyze the realization of philosophy classes in an emancipatory perspectiv